A concept-ontology-based model for resource conflict and task scheduling in concurrent engineering. (June 2017) - Li, Kai; Zhao, Ke; Li, Sha
The competitions among manufacturing include development style, method, and procedure. Product design is a kind of high-level thinking activity which has the characteristics of multi-object and without explicit operator. While concurrent engineering can realize product development mode transformation, due to the complexity of concurrent engineering, designer cannot distinguish ontology connotation from denotation. So, it will inevitably encounter various conflicts during collaborative work, such as time conflict, function conflict, quality conflict, and fund conflict. Based on concept view, this article studies the distinguishability of concept ontology. The conceptual level reasons of conflict are analyzed, and standardized descriptions to resource organization and resource utilization are also given. Then, task decomposition, scheduling, and conflict resolution model are presented with constraints of time, resource, and task. Finally, design structure matrix is used to represent concurrent task structure and optimized by row–column transformation. The model is demonstrated with an example from motorcycle engine design, and the results demonstrate that the proposed model is feasible and will help for conflict resolution and task scheduling in concurrent engineering.